Endothelial senescence mediates hypoxia-induced vascular remodeling by modulating PDGFB expression - Kyi, Priscilla; Hendee, Kathryn; Hunyenyiwa, Tendai; Matus, Kienna; Mammoto, Tadanori; Mammoto, Akiko (Frontiers in Medicine, 2022)
Uncontrolled accumulation of pulmonary artery smooth muscle cells (PASMCs) to the distal pulmonary arterioles (PAs) is one of the major characteristics of pulmonary hypertension (PH). Cellular senescence contributes to aging and lung diseases associated with PH and links to PH progression. However, the mechanism by which cellular senescence controls vascular remodeling in PH is not fully understood. The levels of senescence marker, p16INK4A and senescence-associated β-galactosidase (SA-β-gal) activity are higher in PA endothelial cells (ECs) isolated from idiopathic pulmonary arterial hypertension (IPAH) patients compared to those from healthy individuals. Hypoxia-induced accumulation of a-smooth muscle actin (aSMA)-positive cells to the PAs is attenuated in p16fl/fl-Cdh5(PAC)-CreERT2 (p16idEC) mice after tamoxifen induction. We have reported that endothelial TWIST1 mediates hypoxia-induced vascular remodeling by increasing platelet-derived growth factor (PDGFB) expression. Transcriptomic analyses of IPAH patient lungs or hypoxia-induced mouse lung ECs reveal the alteration of senescence-related gene expression and their interaction with TWIST1. Knockdown of p16INK4A attenuates the expression of PDGFB and TWIST1 in IPAH patient PAECs or hypoxia-treated mouse lungs and suppresses accumulation of aSMA–positive cells to the supplemented ECs in the gel implanted on the mouse lungs. Hypoxia-treated mouse lung EC-derived exosomes stimulate DNA synthesis and migration of PASMCs in vitro and in the gel implanted on the mouse lungs, while p16idEC mouse lung EC-derived exosomes inhibit the effects. These results suggest that endothelial senescence modulates TWIST1-PDGFB signaling and controls vascular remodeling in PH.